(untitled) (Raparin Journal of Humanities (RJH), 2026)
much of the information came from the Greek historians. Besides the information about Achaemenid women, these reports included information about the early beginnings of Achaemenid women and how their roles later became more dispersed or scattered, also strange and peculiar information was found in the reports about Achaemenid women in their stories and plays. This view of Achaemenid women by the Greeks was based on two formulas, first, it was because the political tension and constant fighting between Greece and the Achaemenid Empire, and secondly, the big cultural differences between them, especially in how they viewed women. A more accurate understanding began to emerge with the study of primary sources, which is cuneiform texts. In fact, the deciphering of these texts brought a change to researchers’ views on Achaemenid women. This shift began in the late 19th century, following the discovery and translation of clay tablets dating back to the Neo-Babylonian period (626–539 B.C.). Later, from the 1920s onward, extensive archaeological excavations at Persepolis (Takht-e Jamshid) uncovered thousands of inscribed clay tablets and seals, which many of them directly referred to women. These discoveries opened an entirely new perspective on the roles and activities of women in the Achaemenid Empire. The inscriptions revealed that women participated commonly in economic, social, and political life, often working alongside men. They were not only employees but also landowners, factory owners, business managers, artists, and laborers. In this research paper, we have thoroughly examined some of these clay tablets to better understand the significant role women played within the Achaemenid Empire. To do so, we focused on explaining the impact of women from the royal family, those from the royal, and those from outside the palace, each on their own.